1984
DOI: 10.1080/02772248409357032
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and retention of polydimethylsiloxanes (silicones) in fish: Preliminary experiments†

Abstract: Hydrophobicityand bioaccumulation potential of linear and cyclic polydimethylsiloxane (PDMS) oligomers were estimated by reversed-phase liquid chromatography and feeding experiments with guppies (Poecilia reticulata). PDMS concentrations in fish were determined by capillary column gas chromatography and gas chromatography-mass spectrometry. In contrast to polychlorinated biphenyls (PCBs), only very small amounts of PDMS were retained by the fish after six weeks feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 14 publications
(11 reference statements)
1
17
0
Order By: Relevance
“…Tables 6 a, 6 b, and 6 c present the 10g{Kow} values of organosilicon compounds, including linear and cyclic siloxanes and silanols, estimated at room temperature (20-25°C) by LOGKOW [19]. Apparent 10g{Kow} values of linear and cyclic siloxanes estimated by Bruggeman et al [30] are also presented in these tables for comparison. Figure 5 provides a plot of apparent In general, the linear and cyclic organosiloxanes have higher log{Kow} values than silanols.…”
Section: Octanollwater Partition Coefficient (Kow)mentioning
confidence: 98%
See 1 more Smart Citation
“…Tables 6 a, 6 b, and 6 c present the 10g{Kow} values of organosilicon compounds, including linear and cyclic siloxanes and silanols, estimated at room temperature (20-25°C) by LOGKOW [19]. Apparent 10g{Kow} values of linear and cyclic siloxanes estimated by Bruggeman et al [30] are also presented in these tables for comparison. Figure 5 provides a plot of apparent In general, the linear and cyclic organosiloxanes have higher log{Kow} values than silanols.…”
Section: Octanollwater Partition Coefficient (Kow)mentioning
confidence: 98%
“…Apparent hydrophobicity or apparent 10g{K ow } has been estimated for a series of linear and cyclic organosiloxanes by using corrected retention times in reversed phase high performance liquid chromatography (HPLC) [30]. The apparent 10g{K ow } for highly hydrophobic compounds (log {Kow} > 7) may have large errors due to extrapolation involved in the estimation, and should therefore be used with caution.…”
Section: Octanollwater Partition Coefficient (Kow)mentioning
confidence: 99%
“…Bruggeman et al (1984) report the results of an earlier study [de Groot (1979), in Dutch] that found traces of D4 in water from the River Rhine in 1979.…”
Section: Measured Environmental Concentrationsmentioning
confidence: 86%
“…The first study (Bruggeman et al, 1984) determined the log K ow to be 4.45 using a high performance liquid chromatography (HPLC) retention time method. A homologous series of n-alkylbenzenes were used as reference compounds.…”
Section: N-octanol-water Partition Coefficientmentioning
confidence: 99%
See 1 more Smart Citation